Comparison of immune persistence among inactivated and live attenuated hepatitis a vaccines 2 years after a single dose. Issue 9 (1st September 2016) - Zhang, Xiaoshu; An, Jing; Tu, Aixia; Liang, Xuefeng; Cui, Fuqiang; Zheng, Hui; Tang, Yu; Liu, Jianfeng; Wang, Xuxia; Zhang, Ningjing; Li, Hui
ABSTRACT: Objective : Compare immune persistence from one dose of each of 3 different hepatitis A vaccines when given to school-age children: a domestic, live attenuated hepatitis A vaccine (H2 vaccine); a domestic inactivated hepatitis A vaccine (Healive®); and an imported, inactivated hepatitis A vaccine (Havrix®), .Methods : School-age children were randomized into 1 of 4 groups to receive a single dose of a vaccine: H2 vaccine, Healive®, Havrix®, or hepatitis B vaccine [control]. Serum samples were collected 12 and 24 months after vaccination for measurement of anti-HAV IgG using microparticle enzyme immunoassay. Seropositivity was defined as ≥ 20 mUI/ml. We compared groups on seropositivity and geometric mean concentration (GMC).Results : Seropositive rates for the H2, Healive®, Havrix®, and control groups were 64%, 94.4%, 73%, and 1.0%, respectively, 12-months post-vaccination; and 63%, 95.6%, 72%, and 1.0%, respectively 24-months post-vaccination. Seropositivity was greater for Healive® than for H2 and Havrix® at 12 months (p-values < 0.001) and 24 months (p-values < 0.0001). Average GMCs for the H2, Healive®, Havrix®, and control groups, in mIU/ml, were 29.7, 81.0, 36.4, and 2.9, respectively at 12 months, and 30.9, 112.2, 44.3, and 2.9, respectively, at 24 months. GMCs were greater for Healive® than for H2 and Havrix® at 12 months (p-values < 0.0001 and < 0.001, respectively) and 24 months (p-values < 0.001). No statistically significant differences in seropositivity or GMC were found within groups between 12 and 24 months.Conclusion : Immunity persisted 24 months after a single dose of inactivated hepatitis A vaccine and live attenuated hepatitis A vaccine.